Nutritional Status Assessment for displaced children in Dibagah shelter - Fatma Q. Hamamurad; Rafiq M.S. Rashid; Sazan M Haidary (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In developing nations, especially those with unstable security, malnutrition is one of the most pressing public health issues. This research study aimed to identify malnutrition biomarkers (Hemoglobin) and the nutritional status of children under 5 years old. Who was displaced and survived in the dibagah shelter northern part of Iraq. The nutritional status was used for sixty of children, (33) male and (27) female. 12 to 59 months is the age of the children. An interviewer-administered structured questionnaire was used to collect data. Anthropometric measurements were calculated for weight-for-age, height-for-age, and Head-circumference. Therefore, the nutritional status of children compared to the standard growth of children was published by World Health Organization (WHO) in 2006. For the hematological test, Hemoglobin level (Hb) was measured. The findings indicated a high prevalence of nutritional status. Our study indicated that the nutritional status of children was slightly poor, the growth rate of males from 12-24 months was 11.56 g/day but for females were 7.45 g/day. Mostly the results for all groups were plotted under the 50 percentiles. To the results of the hematological test of children, hemoglobin level was not significant differences (p˃0.05) among the sexes and ages of the periods.